(untitled)
The present study was conducted to evaluate the effects of inorganic fertilizers in combination with constant supply of supplementary feeds on growth and production of exotic carps for a period of one year, from February 2007 to January 2008. Three treatments namely T1 Urea + TSP (2 : 1), 40 kg/ha, T2 Urea + TSP (2 : 1), 60 kg/ha and T3 (Urea + TSP (2 : 1), 80 kg/ha